Patients with large‐duct primary sclerosing cholangitis and Crohn's disease have a better outcome than those with ulcerative colitis, or without IBD. Issue 5 (8th January 2016) - Fevery, J.; Van Steenbergen, W.; Van Pelt, J.; Laleman, W.; Hoffman, I.; Geboes, K.; Vermeire, S.; Nevens, F.
Summary: Background: Approximately 20% of primary sclerosing cholangitis (PSC) patients with concomitant inflammatory bowel disease (IBD) have Crohn's disease (CD). Aim: To compare PSC/CD with other PSC patients. Methods: Retrospective study of 240 PSC patients diagnosed between 1975 and 2012 (median follow‐up 12 years). Activity of PSC at diagnosis was assessed by liver biopsy, Mayo risk and ERC scores. Survival without liver transplantation, number of transplantations and liver‐related death were endpoints. Results: Sixty‐three per cent of patients had IBD: 105 UC, 32 CD and 14 IBD unclassified (IBDu). IBD was diagnosed before PSC in 50%. The yearly development of PSC after diagnosing IBD was similar in UC, CD or IBDu. Small‐duct PSC was present in 28% of PSC/CD compared to 3% of PSC/UC. Small‐duct PSC had a markedly better survival than large‐duct PSC: no patient developed cholangiocarcinoma or liver‐related death, but colorectal cancer occurred in three patients. In large‐duct PSC, a more favourable outcome was evident in patients with CD. The liver disease was less progressive: one patient underwent liver transplantation compared to 28% and liver‐related deaths were absent compared to 7% in the other PSC groups. Conclusions: The prevalence of PSC with concomitant Crohn's disease is relatively rare, but the outcome is more benign than PSC with UC or without IBD. Approximately one‐fourth has small‐duct PSC. In large‐duct PSC/CD, liver disease is less aggressive and the outcome is much better. The outcome of PSC patients with UC resembled that of PSC without IBD.